Understanding Psychological and Psychopathological Facets in Love Addiction: Preliminary Results. - Cavalli, Roberta Gabriella; Tacchino, Camilla; Velotti, Patrizia (Sexual Health & Compulsivity)
Love Addiction (LA) is characterized by obsessive love towards a significant other, yet its conceptualization remains unclear. This study aimed to provide a preliminary framing of LA by examining its psychological and psychopathological facets. From a sample of 720 Italian adults, 36 at-risk individuals were identified and matched with controls, totaling 72 subjects. A multivariate analysis revealed that those at risk of LA scored higher on emotion dysregulation, insecure attachment, anxiety, depression, and stress, while controls scored higher in selfconcept clarity, adaptive emotion regulation, and caregiving behaviors. These findings suggest a multidimensional nature of LA, emphasizing its psychopathological aspects.